Empirical lateral-force-model for forklift tires - Sergey Stepanyuk; Rainer Bruns; Konstantin Krivenkov (Logistics Research, 2017)
Operational safety is the major aspect of a counterbalanced forklift's design. A new test was introduced with the standard DIN EN 16203 to test the lateral dynamic safety of forklifts. The measurements involve high costs and effort to achieve reproducible re-sults. Multibody simulations (MBS) are conducted to facilitate the design of safety systems and understand the safety limits of an industrial truck. An adequate tire model is an essential part of such simulation. A new approach to forklift tire modeling is presented in this paper. It involves measuring several common industrial tires on a drum tire testing apparatus and using them to parametrize the tire model. The SUPREM model (German: Superelastisches Reifenmodell) uses a mathematical modeling approach to describe lateral force and lateral tire deformation based on wheel load, slip angle, slip rate, and driving velocity. For this easy-to-use model, 8 parameters are estimated from tire measurements for different tire types. Better tire approximation leads to more accurate multibody simulations and a deeper understanding of the dynamic behavior of forklifts. Better vehicle lateral stability can be achieved if the outcomes are considered in the design process of a forklift. With this model highly dynamic multibody forklift simulations according to DIN EN 16203 can be carried out.
Keywords: 650; Tires; Modeling; Multibody Simulation; Lateral Force; Lateral Stability